Reasons and obstacles in drug-resistant tuberculosis treatment in Yogyakarta: A qualitative study - Handayani, Nur; Riyandini, Kristi (BKM Public Health and Community Medicine, 2021)
Objective: Drug-Resistant Tuberculosis patients need counseling, psychosocial support, nutrition repair, to even family economic support. The study aims to explore the experience of Drug-Resistant Tuberculosis patients receiving treatment. Method: Qualitative research with a design of phenomenology research. Snowball sampling technique and recruitment via WhatsApp to get informants, then informant chose by purposive sampling according to predetermined inclusion criteria. The study was conducted from April through May 2021 in Yogyakarta. The data is gathered via in-depth interviews of three men who have finished the March 2021 treatment, one woman finished April 2019, and 8 as significant others. Validity of data through triangulation and member literacy. Results: The reason for taking medication, not just for health reasons such as wanting to be healthy, can return to normal activities and not wish to harm others. But it's also for non-health reasons, like the economic factors in which informants are the backbone of the family and the family factor. Financial and psychological factors are internal barriers to tuberculosis. And there are external obstacles such as side effects, stigma, medications, and distance from health care facilities. Conclusion: Health and non - health reasons are factors that prompt the patient to accept treatment. Medical barriers come from within as well as from without. Both patients and families need counseling, health education, and motivation, and psychosocial support. Advanced vocational training and venture capital for cured Drug-Resistant Tuberculosis patients are required to regain their power.